Правові особливості проведення спеціальної операції у сфері державної митної справи “Бастіон” - Федотов, О. П.; Левченко, С. Г.; Fedotov, Oleksii P.; Levchenko, Svitlana G. (Одеса : Гельветика, 2019)
Статтю присвячено дослідженню правового змісту та сутності організаційно- практичних заходів, які здійснюються у сфері державної митної справи митним блоком Державної фіскальної служби України в рамках спеціальної (оглядової) операції “Бастіон”, направленої на попередження, виявлення та припинення незаконного переміщення товарно-матеріальних цінностей (тютюнових виробів, алкогольних напоїв, спирту, паливо-мастильних матеріалів, інших товарів, а також національної та іноземної валюти), і які проводяться у чітко встановлені Державною фіскальною службою України терміни. Акцентовано увагу на ознаках ризикованості митного оформлення товарів, які переміщуються через митний кордон України у зоні діяльності Одеської митниці ДФС, щодо яких скеровано організаційно-практичні заходи у рамках проведення спеціальної (оглядової) операції “Бастіон”. Зроблено висновок про те, що, враховуючи специфіку організаційно- практичних (оперативних) заходів у рамках проведення спеціальної (оглядової) операції “Бастіон”, правове регулювання зазначеного питання потребує суттєвого доопрацювання законодавства України з питань державної митної справи. The paper studies a legal content and essence of the organizational and practical measures that are implemented in the sphere of the state customs affairs by the customs division of the State Fiscal Service of Ukraine (SFS) within a frame of a special (surveillance) operation “Bastion” aimed at prevention, detection and termination of illegal transfer of goods and materials (tobacco products, alcoholic beverages, spirit, fuels and lubricants, other goods as well as the national and foreign currencies) that are performed in the clearly defined periods established by the State Fiscal Service of Ukraine. Attention is paid to the signs of the risks associated with the customs clearance of the goods transferred across the customs border of Ukraine within the activity sphere of Odessa Customs of the SFS which are the subject matter of the organizational and practical measures employed within the frame of the special (surveillance) operation “Bastion”. Based on the analysis of the current legislation of Ukraine concerning the customs affairs, the algorithm for carrying out the special (surveillance) operation “Bastion” was developed within the frame of the state customs affairs. It was established that within the frame of the special (surveillance) operation “Bastion” the exclusive right to carry out the organizational and practical measures is entrusted to the customs division of the State Fiscal Service of Ukraine. In doing so, the interaction mechanism in localities between the customs division of the State Fiscal Service of Ukraine and the tax militia within the frame of the special (surveillance) operation “Bastion” aimed at detection of criminal and other offences in the taxation or customs spheres is improperly adapted to the current legal requirements. It was concluded that with due account of specificity of the organizational and practical measures (operational procedures) of the special (surveillance) operation “Bastion”, the legal regulation of the indicated issue requires substantial improvements of the legislation of Ukraine concerning the state customs affairs.
Федотов О. П., Левченко С. Г. Правові особливості проведення спеціальної операції у сфері державної митної справи “Бастіон” / О. П. Федотов, С. Г. Левченко // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА Святий Миколай". - Одеса : Видавничий дім «Гельветика», 2019. - № 4. – C. 62-72.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; государственное таможенное дело; таможня ДФС Украины; организационно-практические мероприятия; державна митна справа; митниця ДФС України; state customs affairs; customs of the SFS of Ukraine